2a^2 + 2 a+1 3(a-1)
- + = формула разность квадратов; общий знаменатель 2(a-1)(a+1)
(a-1)(a+1) a-1 2(a+1)
4a^2 + 4 - 2(a+1)(a+1) + 3(a-1)(a-1)
= формула квадрат разности
2(a-1)(a+1)
4a^2 + 4 - 2a^2 - 4a - 2 + 3a^2 - 6a + 3
=
5a^2 - 10a + 5
5(a^2 - 2a + 1)
5(a - 1)^2
5(a - 1)
2(a+1)
2a^2 + 2 a+1 3(a-1)
- + = формула разность квадратов; общий знаменатель 2(a-1)(a+1)
(a-1)(a+1) a-1 2(a+1)
4a^2 + 4 - 2(a+1)(a+1) + 3(a-1)(a-1)
= формула квадрат разности
2(a-1)(a+1)
4a^2 + 4 - 2a^2 - 4a - 2 + 3a^2 - 6a + 3
=
2(a-1)(a+1)
5a^2 - 10a + 5
=
2(a-1)(a+1)
5(a^2 - 2a + 1)
= формула квадрат разности
2(a-1)(a+1)
5(a - 1)^2
=
2(a-1)(a+1)
5(a - 1)
2(a+1)